The caring class : home health aides in crisis - Schweid, Richard, 1946- (Culture and politics of health care work., 2021)
"The book is an absorbing look into our home health care system. To write the book, Richard Schweid rented an apartment in the Bronx, sat in on training courses provided by Cooperative Health Care Associates for home health aides, and lived among those he was interviewing. With one compelling story after another, Schweid introduces us to the people who take these jobs and gives us a visceral sense of what home health care entails, the agencies that provide it, the policies that regulate it, and the clients who receive it."--